Introductory thermal concept evaluation: Assessing students' understanding - Yeo, Shelley; Zadnik, Marjan (The American Association of Physics Teachers, 2001)
We describe a pen and paper instrument designed to provide a measure of a range of student beliefs about thermal phenomena. The trial version, administered to 478 high school and university students aged 15–18 years, was able to distinguish belief changes in two populations, year 11 and first-year university physics students. We have used the revised instrument as a pre-test and post-test for evaluating students’ conceptual change following instruction. The instrument, called the Thermal Concept Evaluation, is appended.